Best Practice Kepemimpinan Kepala Sekolah dalam Menciptakan Iklim Belajar Jarak Jauh yang Kondusif - Retno Miasih; Enung Hasanah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to explore the leadership style of the principal at SD Muhamamdiyah 2 Blawong in creating a conducive learning climate during learning from a distance amids the pandemic covid-19. This study used a descriptive method with a qualitative approach. The research subjects consisted of principals, school committees, classroom teachers, and parents. Data collection techniques were carried out through in-depth individual interviews, environmental observations, and document analysis. All data collected were analyzed using qualitative analysis methods. Based on the results of the study, it could be seen that the learning climate implemented at SD Muhammadiyah Blawong 2 was very conducive to learning from a distance. The results of this study indicate that it was inseparable from the leadership role of the school principal who was adaptive, prioritized cooperation, fair, and has the perfect attitude to build a conducive learning climate. This was also inseparable from the ability of the principal in getting support from the parents of students. Therefore, school principals should always try to increase creativity in adapting any changes that occur.